CHRONIC PELVIC PAIN SYNDROME IN WOMEN WITH VAGINAL DYSBIOSIS: A SYSTEMATIC REVIEW OF PRESENTATION, DIAGNOSIS, AND MANAGEMENT - Agata Panfil; Agata Lurka; Hanna Pietruszewska; Katarzyna Kleszczewska; Agnieszka Pruska; Natalia Senatorska; Julia Rarok; Daria Godlewska; Monika Banaszek; Julia Błocka (International Journal of Innovative Technologies in Social Science, 2025)
Background: Chronic pelvic pain syndrome (CPPS) with vaginal dysbiosis is challenging to diagnose and can significantly affect women’s health and daily life. Objective: To review recent research on the symptoms, diagnosis, and treatment of CPPS with vaginal dysbiosis, and to summarize new findings and clinical practices. Methods: Articles from PubMed, Scopus, and Google Scholar published between 2000 and 2025 were included. The review focused on original studies and systematic reviews involving adult women with CPPS and vaginal microbiota assessment. Case reports, non-English articles, and studies lacking vaginal microbiota analysis were excluded from the analysis. Data extraction and quality assessment were conducted using the Newcastle-Ottawa Scale and AMSTAR 2. Results: Women with CPPS and vaginal dysbiosis often experience persistent pelvic pain, sexual and urinary symptoms, and emotional distress. Diagnosis typically includes clinical examination, laboratory testing, and vaginal microbiota analysis using bacterial or genetic methods. Treatment may involve antibiotics, microbiota restoration, physical therapy, and mental health support. Advances in vaginal microbiome research and precision medicine are expected to shape future treatments.